Pulmonary hypertension specific treatment in infants with bronchopulmonary dysplasia. Issue 1 (22nd June 2016) - Kadmon, Gili; Schiller, Ofer; Dagan, Tamir; Bruckheimer, Elchanan; Birk, Einat; Schonfeld, Tommy
Summary: Objective: When bronchopulmonary dysplasia (BPD) is complicated by pulmonary hypertension (PH), morbidity and mortality are significantly increased. BPD‐associated PH is not included in the current indications for PH medications. However, limited data demonstrate hemodynamic improvement and decreased mortality with PH‐specific treatment. This report describes our 6‐year experience treating BPD‐associated PH with PH medications, mainly sildenafil. Study design: The medical records of 20 infants diagnosed with BPD‐associated PH at a tertiary pediatric pulmonary hypertension clinic in 2008–2014 were reviewed. Clinical improvement was defined as a decrease in Ross functional class by at least one degree. PH severity was classified by echocardiography as mild, moderate, or severe. Hemodynamic improvement was defined as a decrease in PH severity by at least one level. Results: Eighteen out of 20 patients were treated with PH medications: 12 sildenafil, 5 sildenafil and bosentan, and 1 bosentan. Median follow‐up time was 2 years. Mean functional class significantly decreased from 3.2 ± 0.9 at diagnosis to 1.7 ± 0.9 at the last follow‐up. Improvement in functional class was observed in 15/16 children (94%). Moderate or severe PH was found in 13/18 children (72%) at diagnosis, and in three (17%, all moderate PH) at the last follow‐up. Improvement in PH class by echocardiography was demonstrated in 14/18 children (78%). The survival rate was 95%. Conclusion: Treatment of BPD complicated by PH with PH‐specific medications, mainly sildenafil, is associated with improvement in both clinical and hemodynamic parameters and a low mortality rate.Pediatr Pulmonol. 2017;52:77–83. © 2016 Wiley Periodicals, Inc.